Tiger abundance and ecology in Jigme Dorji National Park, Bhutan - Pema Dendup; Choki Lham; Wangchuk Wangchuk; Yonten Jamtsho (Global Ecology and Conservation, 2023)
Conservation of large carnivores, especially, wild tigers (Panthera tigris) require an accurate population estimate and knowledge of their ecology. Camera traps have been widely used to estimate the population abundance of animals with unique natural markings, cryptic behaviour, and low population density. This study aimed to assess tiger abundance and density, home range, and activity pattern in Jigme Dorji National Park (JDNP), Bhutan. We carried out camera traps from October 2021 to January 2022. A total of 56 camera stations (a pair in each station) was installed in a 5 × 5 km2 grid along the latitudinal gradient of 1200–4300 m. With the sampling effort of 1528 trap nights, 478 tiger images were captured in 12 stations (21.4 % of the camera stations). Their unique stripe patterns identified six tigers (4 male and 2 female). We estimated tiger abundance of 15.16 ± SE 5.41 (9.13–32.79) and a density of 0.263 ± SE 0.115 (0.116–0.601 individuals) per 100 km2. The home range analysis at 50 % kernel density estimators indicated 151 km2 and 90 km2 as the home range for the male and the female tiger, respectively. The activity pattern of the tigers in JDNP indicated crepuscular type with peak activity in 17:00–18:00 h. The tiger activity pattern strongly overlaps with the activity pattern of the Himalayan serow (Capricornis thar). The current study ascertains JDNP as an important tiger conservation area and can be a source for tiger population for other protected areas and Territorial Divisions. We recommend timely monitoring of tiger and their prey base population, and habitat through enhanced Spatial Monitoring and Reporting Tool (SMART) patrolling programs..